PERTUMBUHAN BIBIT GENERASI M-1 TANAMAN PADI GOGO (Oryza sativa L.) VARIETAS LOKAL DENGAN PERLAKUAN MUTAGEN ETHYL METHANE SULFONATE (EMS) - Wahyudhi, Aditya; Nurhidayah, Tengku (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
This study aimes of determine the effect of mutagen Ethyl Methane Sulfonate (EMS) on upland local rice (Oryza sativa L.) varieties at generation M-1. This research has been carried out at the Department of Agrotechnology Greenhouse, Faculty of Agriculture, University of Riau, in November to December 2013. The research used factorial Completely Randomized Design consisting of two factors, namely two local rice varieties and five concentrations of mutagens EMS and four replications. The mean deviation between treatments tested by Duncan New Multiple Range Test (DNMRT) at the level of 5%. Parameters observed were time of first tiller appeared, lamina length, midrib length, seedling height, number of leaves, number of tillers, number of life seedling, the number of variegate seedling. Results indicated that the mutagen EMS at a concentration of 1%, reduced the number of first seedling appear, decreasing plant height, number of tillers and total life seeds. Â Keywords: Upland rice, Ethyl Methane Sulfonate.